Munie's Snack / Munirah Mohd Radzi - Mohd Radzi, Munirah (2016)
Munie's Snack is a new local company that located in Puchong, Malaysia. The name of this company is come out from the nick name of the owner which named Munirah Binti Mohd Radzi. The journey is begin on April, 2018 when I start to make a very delicious cookies by my own recipe for Hari Raya festive, but after too much demanding on my cookies I decide to continuously produce a cookies all the time. On February 2019, I start to doing hardly promotion by creating a Facebook page for my brand.